Perceptions of obesity as a health risk: psychometric scale development and relationship with behavioural intentions - Swift, Judy Anne (2006)
Obesity represents a serious threat to health which can be reduced by volitional control of eating and physical activity behaviour. Social cognition theories propose that such behaviour is influenced by cognitions regarding its desirability. The role of obesity outcome expectancies in predicting weight control behaviour has not been established and there are no psychometrically sound measures of these constructs.